Microsoft Azure : planning, deploying, and managing your data center in the cloud /: planning, deploying, and managing your data center in the cloud. (2015) - Copeland, Marshall; Soh, Julian; Puca, Anthony; Manning, Mike; Gollob, David
No abstract available